Knowledge, attitudes, and practices related to COVID-19 pandemic among adult population in Sidama Regional State, Southern Ethiopia: A community based cross-sectional study - Yoseph, Amanuel (PLoS One, 2021)
INTRODUCTION: COVID-19 incidence is increasing and different measures have been adopted to control the spread of the pandemic in Ethiopia. Among these measures, enhancing the knowledge, positive attitudes, and proper practices of prevention measures about the disease is a basic strategy to control it. However, community compliance to control measures is largely dependent on their knowledge, attitudes, and practices (KAP) towards COVID-19. OBJECTIVE: To assess the current level of KAP towards COVID-19 pandemic and predictors among the rural dwellers in Sidama regional state, Southern Ethiopia; 2020. METHODS: This community-based prospective cross-sectional study was carried out from May 1–30, 2020 on a sample of 1,278 adult populations in Sidama regional state, Southern Ethiopia. A multi-stage sampling technique was used to choice the study participants. The data were collected using a structured interviewer-administered questionnaire. We have entered data using Epi data version 3.1 and all analyses were done using SPSS version 25. KAPs scores of study participants based on their independent variables were compared using Chi-square test, t-test or one-way analysis of variance (ANOVA) as required. Bi-variable and multivariable logistic regression analyses were used to identify factors associated with KAP. The important assumptions of the logistic regression model were checked to be satisfied. Adjusted odds ratios (AOR) with a 95% confidence interval (CI) were calculated to assess the existence and strength of associations. RESULTS: From a total of 1,214 study participants, the overall attained knowledge, attitude and practice score about COVID-19 were 90%, 82.4% and 65%, respectively. Among these, 43.9%, 37.5%, and 24.4% of the study participants had demonstrated good knowledge, high attitude and proper practice, respectively. The mean knowledge scores were significantly different between sex, categories of marital status, educational levels, main occupation, and the monthly income quintiles of the study participants (p<0.05). Similarly, the mean attitude scores significantly varied across educational levels, main occupations and marital status (p<0.05). Based on multivariable logistic regression analysis, main occupation of the government employees, education level of diploma and above, highest and second highest wealth rank were positively associated with COVID-19 prevention and control practice. CONCLUSIONS: The majority of study participants had showed good knowledge and optimistic attitude toward COVID-19. But, the level of practice lower than that expected to maximize effective control measures. Further public education interventions and community sensitization campaigns are required for rural adult population in the Sidama regional state, Ethiopia.